Quality of work life and employee efficiency in public and private hospitals in Kenya - Mabele, Trinner Mukamba; Kinyua, Jesse Maina; Bengat, Joseph Kipyegon (University of Embu, 2025)
this study aimed to compare the influence of quality of work life on employee efficiency in public and private level 5 and 6 hospitals in Kenya. a cross-sectional descriptive research design and correlation research design were adopted. Primary data were collected, using structured questionnaires, from 370 respondents, from ten level 5 and two level 6 hospitals in Kenya. Descriptive and inferential statistics were used to analyze data. hypothesis was tested at 5% significance level. the findings revealed a positive linear significant influence of quality of work life on employee efficiency in both public and private level 5 and 6 hospitals in Kenya. it was therefore concluded that enhancement of quality of work life results in improved employee efficiency in both public and private hospitals in Kenya. the study recommends that both public and private hospitals in Kenya enhance their quality of work life in terms of flexible working arrangements and opportunities for personal career growth in order to boost employee efficiency. the study makes substantial contributions to the existing literature on the quality of work life and employee performance, as well as provide useful input in policy formulation in hospitals. PUBLIC INTEREST STATEMENT ARTICLE HISTORY Received 30 May 2024 Revised 18 november 2024 accepted 7 april 2025 KEYWORDS Quality of work life; employee efficiency; public and private hospitals; flexible working arrangements; career growth SUBJECTS the levels 5 and 6 facilities are the highest classifications for hospitals in Kenya. Kenyan hospitals are categorized into six levels (levels 1– 6). the difficult working conditions in Kenyan hospitals have highlighted concerns over worker performance. level 5 and level 6 hospitals receive many patients because they also deal with referral cases. consequently, these two top-tier Kenyan hospitals have higher number of staff and patients compared to lower levels 1 to 4 hospitals. level 1 through level 5 public hospitals are overseen by Kenya’s 47 county administrations, while level 6 public hospitals fall under the national government’s jurisdiction. Private and public hospitals have managerial and operational differences due to their nature,
Keywords: Quality of work life; employee efficiency; public and private hospitals; flexible working arrangements; career growth; human Resource Management; Organizational studies; human Resource Development